Prefrontal Control of Trace Versus Delay Eyeblink Conditioning: Role of the Unconditioned Stimulus in Rabbits (Oryctolagus cuniculus) - Oswald, Barbara; Knuckley, Bryan; Mahan, Kathleen (Behavioral Neuroscience, 2006)
The conditioned eyeblink (EB) response was studied with trace conditioning procedures in rabbits (Oryctolagus cuniculus) with lesions to the medial prefrontal cortex (mPFC) or sham lesions. Three experiments were performed in which either periorbital shock or a corneal airpuff served as the unconditioned stimulus (US) in separate groups of sham or mPFC-lesioned rabbits. Acquisition of the EB conditioned response (CR) was faster and reached a higher asymptote with the eyeshock US than with the airpuff US. However, mPFC lesion-induced trace conditioning deficits were obtained only in the groups that received the airpuff US. All rabbits showed normal delay conditioning and extinction. These results suggest that mPFC mediates trace EB conditioning when emotional arousal is low. However, in circumstances when emotional arousal may be high (i.e., during exposure to aversive periorbital shock), other structures (such as amygdala) may be activated to permit learning even in the absence of input from mPFC. Reprinted by permission of the publisher.